Building Heaven on Earth: Islamic Value in Urban Development - Mohamad, Jamilah (Jurnal Usuluddin, 1998)
Rapid urbanization throughout the world is one of the most important phenomena in recent world history. The term urbanization refers to a two-phase process involving, firstly, the movement of people from rural to urban places where they engage in primarily non-rural functions or occupations, and secondly, the change in their life-styles from rural to urban with its associated values, attitudes and behaviours. Urbanism is a broader concept which is used to refer to all aspects (political, economic, social, etc.) of the urban way of life. Unlike urbanization, urbanism is not a process of urban growth, but rather the end result of urbanization.